Nihonjinkai – a associação dos imigrantes japoneses de Santa Maria/RS – século XX - Silva, Alexandra Begueristain da (2019)
The present thesis of the Graduate Program in History, of the Federal University of Santa Maria, presents the description, the stages covered and the results obtained during four years of research. The object of study is the Association of Japanese Immigrants of Santa Maria/RS and its contribution to the maintenance of the ethnic identity of the group studied. The thesis entitled "Nihonjinkai – The Association of Japanese Immigrants of Santa Maria / RS – Century XX", we worked with the categories of Memory and Identity in researching the history of the Japanese association, as well as the formation of an ethnic identity that came from the contact of the immigrant culture with the Brazilian culture. In order to do so, we sought to build a historical panorama of japanese immigration in Brazil and in Rio Grande do Sul until the official arrival of the first immigrants to the city of Santa Maria. Considering that, although they emigrated in the period after World War II, they emigrated to Brazil with the same objective as the first immigrants, who arrived in 1908, to raise funds and return to their country of origin in a maximum of five years. Through interviews and under the method of oral history that could be observed through the memories they tell, the reasons why their ethnic identity remains much in an intimate and familiar sphere. We seek to understand Nihonjinkai as a space of sociability, demarcation of differences and maintenance of ethnic identity, over these fifty years. We attempted to visualize the possibilities of continuity or not of the entity through the maintenance of the traditional events organized from the beginning of the association in Santa Maria and through the interest or not by the succession on the part of the second generation. Finally, after seeking theoretical references that could confirm or refute the result of inferences and interpretations about Nihonjinkai it was proposed a characterization through a division into four different historical periods, which are: Ascension, stability, decline and resumption. And finally, the conception of cultural "interlacement" is discussed, in which identities pass freely, without the exclusion or overlapping of one another, resulting in the identity of the hyphen, the japanese-brazilian.